(untitled) (Altre Modernità, 2012)
“At the gate” is the closing piece in J. M. Coetzee’s collection of short stories Elizabeth Costello (2003). It depicts Costello, fictitious novelist and prominent character in Coetzee’s late production, and the Kafkaesque waiting-room for Paradise she finds herself in. The first aim of this essay is an exploration of this ambiguous afterlife: surprisingly and disappointingly mundane, it defies traditional expectations. Costello’s afterlife is also a meta-literary construct, and explicitly so. It displays itself as a purgatory of clichés and poor literary imitations, and thus allows Coetzee to expose the limits of literary representation. Costello stands before a gate to Paradise; she is required a statement of belief to pass through, but she feels unable to provide it. She is a writer and, as such, maintains beliefs only provisionally. More than once, though, she is confronted with the idea that having beliefs is what makes us humans. The resulting division between the human and the writing self, and the impossibility of Paradise for the latter, are dealt with in the second part of this essay. Identity and its persistence are central themes in Coetzee’s works. In the last part of this essay, "At the Gate" is compared to some of them – most notably, to some sections of Diary of a Bad Year (2007), since there, too, the main character is an author reasoning on the afterlife.